Management of Poisonings in Children - Puneet Aulakh Pooni; Vikas Bansal (Wolters Kluwer Medknow Publications, 2016)
Acute poisoning in children is common problem worldwide, prevalent in rural as well as urban areas. Exposure of a child to such a substance is usually accidental and can cause symptoms and signs of organ dysfunction leading to injury or death. This review is intended to discuss general approach to various types of accidental poisoning based on altered physiology in general and history and a physical examination with intent to fit the clinical characteristics into a group of signs and symptoms associated with a particular substance. (also known as TOXIDROMES) Fortunately, very few patients require hospital admission and even fewer patients need treatment in a pediatric Intensive care unit. Most patients will need a period of observation in a monitored bed which could be located in the emergency ward or in a step down level of pediatric intensive care unit The ones who need admission to pediatric intensive care unit are usually critical if organ dysfunction sets in. The challenge to the pediatric Intensivist tends to be institution of supportive treatment promptly, as well as, to institute specific antedote therapy (if available) as soon as feasible. To the physician examining the patient a challenging issue is to determine which ingestions are potentially high risk and which are Inconsequential. Alluminium phosphide, organophosphorous compounds, kerosens oil ingestion can result in life threatening problems in affected children, are therefore reviewed in greater detail. Most poisonings can be managed by supportive treatment in the PICU.